2005
DOI: 10.1007/s00784-005-0010-7
|View full text |Cite
|
Sign up to set email alerts
|

A 2-year clinical evaluation of sealed noncavitated approximal posterior carious lesions in adolescents

Abstract: The objective was to evaluate the clinical performance of a therapeutic sealant to arrest the progression of noncavitated approximal posterior carious lesions. The study population comprised 50 adolescents in whom bitewing radiographs had been taken for diagnosis of caries. Approximal noncavitated lesions in premolars and molars (4d-7m) were selected. One group (n=17) had a sealant placed after tooth separation on all enamel lesions. A second group (n=7) received sealant and fluoride varnish in a split-mouth d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
1
11

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 20 publications
3
57
1
11
Order By: Relevance
“…The present investigation did not detect any significant difference between the experimental and control groups, which is contrary to the findings of previous studies 3,4 One of the reasons that might explain this lack of difference between the groups in the present study is the short follow-up period. Gomez et al 3 followed-up the participants over a 2-year period, while the follow-up by Martignon et al 4 was an 18-month period.…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…The present investigation did not detect any significant difference between the experimental and control groups, which is contrary to the findings of previous studies 3,4 One of the reasons that might explain this lack of difference between the groups in the present study is the short follow-up period. Gomez et al 3 followed-up the participants over a 2-year period, while the follow-up by Martignon et al 4 was an 18-month period.…”
Section: Discussioncontrasting
confidence: 57%
“…For instance, one study found that caries lesions measured by radiographic assessment were more likely to regress under intact sealants than under defective sealants. 7 There are two technical aspects of the present study that differed from those of Gomez et al 3 and Martignon et al 4 The first was the use of rubber dam isolation in all cases in order to avoid contamination of the restorative field; and the second was the method used for tooth separation. While the previous authors used orthodontic elastic bands two days before the sealing procedure, in the present study, metal separators were used.…”
Section: Discussionmentioning
confidence: 39%
See 3 more Smart Citations